Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

Climate, peace, and conflict—past and present: Bridging insights from historical sciences and contemporary research - Sam White; Dominik Collet; Agustí Alcoberro; Mariano Barriendos; Rudolf Brázdil; Pau Castell; Siyu Chen; Cedric de Coning; Dagomar Degroot; Lukáš Dolák; Stefan Döring; Santiago Gorostiza; et al. (Ambio, 2025)
Concern has risen that current global warming and more frequent extreme events such as droughts and floods will increase conflict around the world. This concern has spurred both social science research on contemporary climate, peace, and conflict as well as research in the historical sciences on past climate, weather, warfare, and violence. This perspectives article compares these two fields of scholarship and examines how each may benefit the other. It finds significant convergences in methods and insights across contemporary and historical research as well as persistent patterns in causal pathways between climate and conflict. Contemporary climate, peace, and conflict (CPC) research may sharpen methods and causal models for historical researchers. Historical studies, particularly those informed by contemporary research, may elucidate deep origins and long-term effects of climate-related conflicts. For policymakers and the public, history offers comprehensible ways to make sense of complex and contingent linkages and to construct cogent narratives of the past as well as storylines for the future.

Pericardium decellularization in a one-day, two-step protocol - P. López-Chicón; J. I. Rodríguez Martínez; C. Castells-Sala; L. Lopez-Puerto; L. Ruiz-Ponsell; O. Fariñas; A. Vilarrodona (Molecular and Cellular Biochemistry, 2025)

Optimization of resolution as a simultaneous function of solvent composition, pH and temperature in reversed-phase liquid chromatography - Sebastian J. Caruso; Pedro N. Cifuente; Cecilia B. Castells; Leonardo G. Gagliardi (Analytica Chimica Acta, 2024)

Last twenty-years activity of cardiovascular tissue banking in Barcelona - C. Castells-Sala; M. L. Pérez; E. Agustí; A. Aiti; E. Tarragona; A. Navarro; J. Tabera; O. Fariñas; J. L. Pomar; A. Vilarrodona (Cell and Tissue Banking, 2024)
The Barcelona Tissue Bank was established from the merge of two previous multi-tissue banks. Potential donors are screened by Donor Center staff and multi-tissue retrieval is performed by specialized own teams. Tissue processing and preservation is performed in clean room facilities by specialised personnel. After quality control of both donor and all tissues results, the heart valves and vascular segments are stored until medical request. The aim of this report is to present the cardiovascular tissue activity and retrospectively evaluate the outcomes of the changes performed in last 20 years. Cardiovascular tissue from 4088 donors was received, specifically 3115 hearts and 2095 vascular segments were processed and evaluated. A total of 48% of the aortic valves, 68% of the pulmonary valves and 75% of the vascular segments were suitable for transplant. The main reason for discarding tissue was macroscopic morphology followed by microbiological results, for both valves and arteries. Altogether, 4360 tissues were distributed for transplantation: 2032 (47%) vascular segments, 1545 (35%) pulmonary valves and 781 (18%) aortic valves. The most common indication for aortic valve surgery was the treatment of endocarditis, while for pulmonary valves, it was congenital malformation reconstruction. Vascular segments were mainly used for reconstruction after ischemia. During this period, a number of changes were made with the goal of enhancing tissue quality, safety and efficacy. These improvements were achieved through the use of a new antibiotic cocktail, increasing of donor age criteria and changing the microbiological control strategy.

P16-55: Using Metabolomics to Uncover Ontogeny of Drug-Induced Hepatotoxicity and Underlying AOP Mechanisms - T. Martinez-Sena; E. Moro; M. Moreno Torres; G. Quintas; J. Hengstler; R. Jover; J. V. Castell Ripoll (Toxicology Letters, 2023)

Evaluation and assessment of clique arrangements for the estimation of omnipolar electrograms in high density electrode arrays: an experimental animal model study - Samuel Ruipérez-Campillo; Marina Crespo; Álvaro Tormos; Antonio Guill; Antonio Cebrián; Antonio Alberola; Jakob Heimer; Francisco J. Chorro; José Millet; Francisco Castells (Physical and Engineering Sciences in Medicine, 2023)
High-density catheters combined with Orientation Independent Sensing (OIS) methods have emerged as a groundbreaking technology for cardiac substrate characterisation. In this study, we aim to assess the arrangements and constraints to reliably estimate the so-called omnipolar electrogram (oEGM). Performance was evaluated using an experimental animal model. Thirty-eight recordings from nine retrospective experiments on isolated perfused rabbit hearts with an epicardial HD multielectrode were used. We estimated oEGMs according to the classic triangular clique (4 possible orientations) and a novel cross-orientation clique arrangement. Furthermore, we tested the effects of interelectrode spacing from 1 to 4 mm. Performance was evaluated by means of several parameters that measured amplitude rejection ratios, electric field loop area, activation pulse width and morphology distortion. Most reliable oEGM estimations were obtained with cross-configurations and interelectrode spacings $$\le 2$$ ≤ 2 mm. Estimations from triangular cliques resulted in wider electric field loops and unreliable detection of the direction of the propagation wavefront. Moreover, increasing interelectrode distance resulted in increased pulse width and morphology distortion. The results prove that current oEGM estimation techniques are insufficiently accurate. This study opens a new standpoint for the design of new-generation HD catheters and mapping software.

Biological and molecular characterization of a resistance-breaking isolate of citrus tristeza virus from Uruguay and its effects on Poncirus trifoliata growth performance - Leticia Rubio; Ana Arruabarrena; Matías Salvo; Matías Castells; Ana Bertalmío; Lester Hernández-Rodríguez; María J. Benítez-Galeano; Diego Maeso; Rodney Colina; Fernando Rivas (Archives of Virology, 2023)

Validation of self-reported adherence in chronic patients visiting pharmacies and factors associated with the overestimation and underestimation of good adherence - C. Valdés y Llorca; Ernesto Cortés-Castell; J. M. Ribera-Casado; P. de Lucas-Ramos; L. M. de Palacio-Guerrero; F. Mugarza-Borqué; J. L. Casteig-Ayestarán; J. Díaz-Olmo; A. Casteig-Blanco; V. F. Gil-Guillén; M. Rizo-Baeza (European Journal of Clinical Pharmacology, 2020)

Modeling the Transport of Human Rotavirus and Norovirus in Standardized and in Natural Soil Matrix-Water Systems - P. Gamazo; M. Victoria; J. F. Schijven; E. Alvareda; L. F. L. Tort; J. Ramos; L. A. Lizasoain; G. Sapriza; M. Castells; L. Bessone; R. Colina (Food and Environmental Virology, 2020)

An extensive field study reveals the circulation of new genetic variants of subtype 1a of bovine viral diarrhea virus in Uruguay - L. Maya; M. Macías-Rioseco; C. Silveira; F. Giannitti; M. Castells; M. Salvo; R. Rivero; J. Cristina; E. Gianneechini; R. Puentes; E. F. Flores; F. Riet-Correa; et al. (Archives of Virology, 2020)

Evaluation of Bacterial Contamination as an Indicator of Viral Contamination in a Sedimentary Aquifer in Uruguay - P. Gamazo; M. Victoria; J. F. Schijven; E. Alvareda; L. F. L. Tort; J. Ramos; L. Burutaran; M. Olivera; A. Lizasoain; G. Sapriza; M. Castells; R. Colina (Food and Environmental Virology, 2018)

EACR-MRS conference on Seed and Soil: In Vivo Models of Metastasis - I. Teles Alves; N. Cohen; P. G. Ersan; R. Eyre; I. Godet; D. Holovanchuk; R. Jackstadt; L. Kyjacova; K. Mahal; A. Noguera-Castells; L. Recalde-Percaz; J. P. Sleeman (Clinical & Experimental Metastasis, 2017)

The loss of dispersal on islands hypothesis revisited: Implementing phylogeography to investigate evolution of dispersal traits in Periploca (Apocynaceae) - C. García‐Verdugo; M. Mairal; P. Monroy; M. Sajeva; J. Caujapé‐Castells (Journal of Biogeography, 2017)
Aim The loss of dispersal on islands hypothesis ( LDIH ) posits that wind‐dispersed plants should exhibit reduced dispersal potential, particularly if island populations are old. In this study, we tested this hypothesis using a detailed phylogeographical framework across different geographical scales. Location Mainland and island areas of the Atlantic and Mediterranean regions, including Macaronesia (Canary Islands and Cape Verde) and Mediterranean islands in the strait of Sicily. Methods Forty‐five populations of Periploca laevigata , a wind‐dispersed shrub, were sampled. Plastid and nuclear microsatellite data were used to reconstruct spatio‐temporal patterns of island colonization, and estimates of seed terminal velocity used as a surrogate for dispersal ability under both field and common garden conditions. Results Our findings did not provide evidence of loss of dispersability in any island lineage. In all of the regions considered, dispersal ability was similar on island and mainland populations, or higher on islands. Contrary to LDIH expectations, lineages inferred as the oldest (western Canaries and Cape Verde) converged towards the most dispersive seed phenotype. This pattern was supported by data obtained under common garden conditions. Within the western Canarian lineage, successful dispersal was shown to be very rare among islands and extensive within islands, but dispersability did not vary significantly from older to more recent sublineages. Considering all the study islands, we found a strong, positive correlation between dispersal ability and estimates of within‐island habitat availability. Main conclusions This study suggests that dispersal ability can be favoured on islands, possibly because traits enhancing wind dispersal are positively selected when habitat availability is high. Our results challenge broad generalizations of the LDIH , but we discuss how overlooking species′ phylogeographical history may give rise to misleading conclusions.

The photosynthetic cytochrome c 550 from the diatom Phaeodactylum tricornutum - Pilar Bernal-Bayard; Leonor Puerto-Galán; Inmaculada Yruela; Inés García-Rubio; Carmen Castell; José M. Ortega; Pablo J. Alonso; Mercedes Roncel; Jesús I. Martínez; Manuel Hervás; José A. Navarro (Photosynthesis Research, 2017)

MtDNA metagenomics reveals large‐scale invasion of belowground arthropod communities by introduced species - Francesco Cicconardi; Paulo A. V. Borges; Dominique Strasberg; Pedro Oromí; Heriberto López; Antonio J. Pérez‐Delgado; Juliane Casquet; Juli Caujapé‐Castells; José María Fernández‐Palacios; Christophe Thébaud; Brent C. Emerson (Molecular Ecology, 2017)
Using a series of standardized sampling plots within forest ecosystems in remote oceanic islands, we reveal fundamental differences between the structuring of aboveground and belowground arthropod biodiversity that are likely due to large‐scale species introductions by humans. Species of beetle and spider were sampled almost exclusively from single islands, while soil‐dwelling Collembola exhibited more than tenfold higher species sharing among islands. Comparison of Collembola mitochondrial metagenomic data to a database of more than 80 000 Collembola barcode sequences revealed almost 30% of sampled island species are genetically identical, or near identical, to individuals sampled from often very distant geographic regions of the world. Patterns of mt DNA relatedness among Collembola implicate human‐mediated species introductions, with minimum estimates for the proportion of introduced species on the sampled islands ranging from 45% to 88%. Our results call for more attention to soil mesofauna to understand the global extent and ecological consequences of species introductions.

Solar radiation and functional traits explain the decline of forest primary productivity along a tropical elevation gradient - Nikolaos M. Fyllas; Lisa Patrick Bentley; Alexander Shenkin; Gregory P. Asner; Owen K. Atkin; Sandra Díaz; Brian J. Enquist; William Farfan‐Rios; Emanuel Gloor; Rossella Guerrieri; Walter Huaraca Huasco; Yoko Ishida; et al. (Ecology Letters, 2017)
One of the major challenges in ecology is to understand how ecosystems respond to changes in environmental conditions, and how taxonomic and functional diversity mediate these changes. In this study, we use a trait‐spectra and individual‐based model, to analyse variation in forest primary productivity along a 3.3 km elevation gradient in the Amazon‐Andes. The model accurately predicted the magnitude and trends in forest productivity with elevation, with solar radiation and plant functional traits (leaf dry mass per area, leaf nitrogen and phosphorus concentration, and wood density) collectively accounting for productivity variation. Remarkably, explicit representation of temperature variation with elevation was not required to achieve accurate predictions of forest productivity, as trait variation driven by species turnover appears to capture the effect of temperature. Our semi‐mechanistic model suggests that spatial variation in traits can potentially be used to estimate spatial variation in productivity at the landscape scale.

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

A single dose of a suicidal DNA vaccine induces a specific immune response in salmonids - M L Ogas Castells; J L La Torre; P R Grigera; T V Poggio (Journal of Fish Diseases, 2015)

Do island plant populations really have lower genetic variation than mainland populations? Effects of selection and distribution range on genetic diversity estimates - C. García‐Verdugo; M. Sajeva; T. La Mantia; C. Harrouni; F. Msanda; J. Caujapé‐Castells (Molecular Ecology, 2015)
Ecological and evolutionary studies largely assume that island populations display low levels of neutral genetic variation. However, this notion has only been formally tested in a few cases involving plant taxa, and the confounding effect of selection on genetic diversity ( GD ) estimates based on putatively neutral markers has typically been overlooked. Here, we generated nuclear microsatellite and plastid DNA sequence data in Periploca laevigata , a plant taxon with an island–mainland distribution area, to (i) investigate whether selection affects GD estimates of populations across contrasting habitats; and (ii) test the long‐standing idea that island populations have lower GD than their mainland counterparts. Plastid data showed that colonization of the Canary Islands promoted strong lineage divergence within P. laevigata , which was accompanied by selective sweeps at several nuclear microsatellite loci. Inclusion of loci affected by strong divergent selection produced a significant downward bias in the GD estimates of the mainland lineage, but such underestimates were substantial (>14%) only when more than one loci under selection were included in the computations. When loci affected by selection were removed, we did not find evidence that insular Periploca populations have less GD than their mainland counterparts. The analysis of data obtained from a comprehensive literature survey reinforced this result, as overall comparisons of GD estimates between island and mainland populations were not significant across plant taxa ( N = 66), with the only exception of island endemics with narrow distributions. This study suggests that identification and removal of markers potentially affected by selection should be routinely implemented in estimates of GD , particularly if different lineages are compared. Furthermore, it provides compelling evidence that the expectation of low GD cannot be generalized to island plant populations.

Development and characterization of nuclear microsatellite markers for Parolinia ornata Webb (Brassicaceae), and cross-species amplification in all species described in the Canarian endemic genus Parolinia - M. A. González-Pérez; J. Caujapé-Castells (Conservation Genetics Resources, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

A temperature-controlled spectrometer system for continuous and unattended measurements of canopy spectral radiance and reflectance - Guillaume Drolet; Tom Wade; Caroline J. Nichol; Chris MacLellan; Janne Levula; Albert Porcar-Castell; Eero Nikinmaa; Timo Vesala (International Journal of Remote Sensing, 2014)

Physiology of the seasonal relationship between the photochemical reflectance index and photosynthetic light use efficiency - Albert Porcar-Castell; José Ignacio Garcia-Plazaola; Caroline J. Nichol; Pasi Kolari; Beñat Olascoaga; Nea Kuusinen; Beatriz Fernández-Marín; Minna Pulkkinen; Eija Juurola; Eero Nikinmaa (Oecologia, 2012)

Clinical characteristics and outcomes in familial adenomatous polyposis patients with a long-term treatment of celecoxib: a matched cohort study - Kui Huang; Lia P. Gutierrez; Steffen Bülow; Steven Gallinger; Antoni Castells; Craig J. Eagle; James M. Church (Familial Cancer, 2011)

Risk factors for multidrug-resistant Pseudomonas aeruginosa acquisition. Impact of antibiotic use in a double case–control study - M. Montero; M. Sala; M. Riu; F. Belvis; M. Salvado; S. Grau; J. P. Horcajada; F. Alvarez-Lerma; R. Terradas; M. Orozco-Levi; X. Castells; H. Knobel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

EU research activities in alternative testing strategies: current status and future perspectives - T. Vanhaecke; S. Snykers; V. Rogiers; B. Garthoff; J. V. Castell; J. G. Hengstler (Archives of Toxicology, 2009)

PRI assessment of long-term changes in carotenoids/chlorophyll ratio and short-term changes in de-epoxidation state of the xanthophyll cycle - I. Filella; A. Porcar-Castell; S. Munné-Bosch; J. Bäck; M. F. Garbulsky; J. Peñuelas (International Journal of Remote Sensing, 2009)

Eyecup scope—optical recordings of light stimulus-evoked fluorescence signals in the retina - Thomas Euler; Susanne E. Hausselt; David J. Margolis; Tobias Breuninger; Xavier Castell; Peter B. Detwiler; Winfried Denk (Pflügers Archiv - European Journal of Physiology, 2009)

Using temperature‐dependent changes in leaf scaling relationships to quantitatively account for thermal acclimation of respiration in a coupled global climate–vegetation model - OWEN K. ATKIN; LINDSEY J. ATKINSON; ROSIE A. FISHER; CATHERINE D. CAMPBELL; JOANA ZARAGOZA‐CASTELLS; JON W. PITCHFORD; F. IAN WOODWARD; VAUGHAN HURRY (Global Change Biology, 2008)
The response of plant respiration ( R ) to temperature is an important component of the biosphere's response to climate change. At present, most global models assume that R increases exponentially with temperature and does not thermally acclimate. Although we now know that acclimation does occur, quantitative incorporation of acclimation into models has been lacking. Using a dataset for 19 species grown at four temperatures (7, 14, 21, and 28 °C), we have assessed whether sustained differences in growth temperature systematically alter the slope and/or intercepts of the generalized log–log plots of leaf R vs. leaf mass per unit leaf area (LMA) and vs. leaf nitrogen (N) concentration. The extent to which variations in growth temperature account for the scatter observed in log–log R –LMA–N scaling relationships was also assessed. We show that thermal history accounts for up to 20% of the scatter in scaling relationships used to predict R , with the impact of thermal history on R –LMA–N generalized scaling relationships being highly predictable. This finding enabled us to quantitatively incorporate acclimation of R into a coupled global climate–vegetation model. We show that accounting for acclimation of R has negligible impact on predicted annual rates of global R , net primary productivity (NPP) or future atmospheric CO 2 concentrations. However, our analysis suggests that accounting for acclimation is important when considering carbon fluxes among thermally contrasting biomes (e.g. accounting for acclimation decreases predicted rates of R by up to 20% in high‐temperature biomes). We conclude that acclimation of R needs to be accounted for when predicting potential responses of terrestrial carbon exchange to climatic change at a regional level.

A new monitoring PAM fluorometer (MONI-PAM) to study the short- and long-term acclimation of photosystem II in field conditions - Albert Porcar-Castell; Erhard Pfündel; Janne F. J. Korhonen; Eija Juurola (Photosynthesis Research, 2008)

Population genetics of Matthiola bolleana (Brassicaceae) in the Canary Islands - J. L. Sánchez Doreste; J. Caujapé-Castells; J. A. Reyes-Betancort; S. Scholz (Plant Systematics and Evolution, 2006)

Estimation of atrial fibrillatory wave from single-lead atrial fibrillation electrocardiograms using principal component analysis concepts - F. Castells; C. Mora; J. J. Rieta; D. Moratal-Pérez; J. Millet (Medical & Biological Engineering & Computing, 2005)

Genetic differentiation of three species of Matthiola (Brassicaceae) in the Sicilian insular system - J. L. Sánchez; G. Domina; J. Caujapé-Castells (Plant Systematics and Evolution, 2005)

A high blood lactate induced by heavy exercise does not affect the increase in submaximal $$\dot V{\text{O}}_2 $$ with hyperoxia - F. B. Favier; F. Prieur; O. Grataloup; T. Busso; J. Castells; C. Denis; A. Geyssant; H. Benoit (European Journal of Applied Physiology, 2005)

Molecular evidence of hybridisation between the endemic Phoenix canariensis and the widespread P. dactylifera with Random Amplified Polymorphic DNA (RAPD) markers - M. A. Gonzlez-Prez; J. Caujap-Castells; P. A. Sosa (Plant Systematics and Evolution, 2004)

Space-time diversification of Androcymbium Willd. (Colchicaceae) in western South Africa - J. Caujapé-Castells; R. K. Jansen; J. Pedrola-Monfort; N. Membrives (Plant Systematics and Evolution, 2002)

Carbon‐based secondary and structural compounds in Mediterranean shrubs growing near a natural CO 2 spring - J. Peñuelas; E. Castells; R. Joffre; R. Tognetti (Global Change Biology, 2002)
We studied carbon‐based secondary and structural compounds (CBSSCs) in Myrtus communis, Erica arborea, and Juniperus communis co‐occurring in a natural CO 2 spring site and in a nearby control site in a Mediterranean environment. Leaf concentrations of phenolics and CBSSCs, such as lignin, cellulose, and hemicellulose, total nonstructural carbohydrates (TNCs), and lipids were measured monthly (phenolics) and every two months (the other compounds) throughout a year. There was a slight seasonal trend towards maximum concentrations of most of these CBSSCs during autumn–winter and minimum values during the spring season, particularly in Myrtus communis . For most of the CBSSCs and species, there were no consistent or significant patterns in response to the elevated [CO 2 ] ( c. 700 μmol mol −1 ) of the spring site. These results were not due to a dilution effect by increased structural or nonstructural carbon. Therefore, in contrast to many experimental studies of CO 2 enrichment, mainly conducted for short periods, there were no greater concentrations of phenolics, and, as in many of these studies, there were neither greater concentrations of the other CBSSCs. These results do not agree with the predictions of the carbon source‐sink hypotheses. Possible causes of this disagreement are discussed. These causes include the complex heterogeneous environmental conditions and the variability of resource availabilities in the field, photosynthetic down‐regulation, and/or the homeostatic and evolutionary nature of organisms. These results suggest evolutionary adaptive responses to changes in CO 2 . They also suggest caution in attributing increased CBSSC concentrations to elevated [CO 2 ] at long‐term scale in natural conditions, and therefore in their implications for plant–herbivore interactions and for decomposition.

Relative influence of biological versus historical factors on isozyme variation of the genus Androcymbium (Colchicaceae) in Africa - N. Membrives; J. Pedrola-Monfort; J. Caujapé-Castells (Plant Systematics and Evolution, 2001)

Cytochemical demonstration of modification of carbohydrates in the mouse zona pellucida during folliculogenesis - M. Avilés; M. El-Mestrah; L. Jaber; M. T. Castells; J. Ballesta; F. W. K. Kan (Histochemistry and Cell Biology, 2000)

The gp49A gene has extensive sequence conservation with the gp49B gene and provides gp49A protein, a unique member of a large family of activating and inhibitory receptors of the immunoglobulin superfamily - M. J. McCormick; M. C. Castells; K. F. Austen; H. R. Katz (Immunogenetics, 1999)

A system to simulate gas exchange in humans to control quality of metabolic measurements - F. Prieur; T. Busso; J. Castells; R. Bonnefoy; H. Benoit; A. Geyssant; C. Denis (European Journal of Applied Physiology, 1998)

Time-resolved fluoroimmunoassays with monoclonal antibodies for rapid identification of parainfluenza type 4 and mumps viruses - J. C. Hierholzer; Patricia G. Bingham; E. Castells; R. A. Coombs (Archives of Virology, 1993)

NCI-H292 as an alternative cell line for the isolation and propagation of the human paramyxoviruses - Empar Castells; Velma G. George; J. C. Hierholzer (Archives of Virology, 1990)